Design and Development of a PPM Control System for Aeroponic Lettuce Plant Nutrient Based on Microcontrollers and Internet of Things - Adi Chandranata; Dedi Kurniadi; Fiky Aryananda (International Journal Labs, 2024)
In the current era, land for farming is increasingly decreasing because the population is so large that agricultural land is being converted into residential land. To enable people to continue farming, especially in urban areas, one of the existing solutions is to use the aeroponic method. In this research, the Internet of Things-based aeroponic lettuce plant nutrition control system found that the TDS sensor was able to maintain the stability of the ppm value of the solution (560-840) ppm according to the needs of the lettuce plant by triggering a peristaltic pump to actively fill the nutrient solution when the ppm value was detected below the set point. The DHT22 sensor is capable of detecting temperatures in the range of 27-33°C and humidity of 70% - 95%. The ultrasonic sensor in the system is used to measure the water level in the box. In this system, to regulate the level of the nutrient solution using a TDS sensor, an average reading value of 675.08 ppm was obtained. The duration of watering and the level of the nutrient solution are done automatically and can be monitored via smartphone so there is no need to check manually every day.